2021
DOI: 10.1097/aln.0000000000003725
|View full text |Cite
|
Sign up to set email alerts
|

Balanced Opioid-free Anesthesia with Dexmedetomidine versus Balanced Anesthesia with Remifentanil for Major or Intermediate Noncardiac Surgery

Abstract: Background It is speculated that opioid-free anesthesia may provide adequate pain control while reducing postoperative opioid consumption. However, there is currently no evidence to support the speculation. The authors hypothesized that opioid-free balanced anesthetic with dexmedetomidine reduces postoperative opioid-related adverse events compared with balanced anesthetic with remifentanil. Methods Patients were randomized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
159
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(176 citation statements)
references
References 40 publications
10
159
6
1
Order By: Relevance
“…After a review of the titles and abstracts, 81 studies were selected and assessed for potential inclusion into this systematic review. After reading the full-text articles, 33 RCTs (published between 1994 and 2021) including 2209 participants were finally included ( Figure 1 ) [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. No unpublished trials were identified with our eligibility criteria in the clinicaltrial.gov register.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After a review of the titles and abstracts, 81 studies were selected and assessed for potential inclusion into this systematic review. After reading the full-text articles, 33 RCTs (published between 1994 and 2021) including 2209 participants were finally included ( Figure 1 ) [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. No unpublished trials were identified with our eligibility criteria in the clinicaltrial.gov register.…”
Section: Resultsmentioning
confidence: 99%
“…The median target sample size was 60 [ 27 , 28 , 29 , 30 , 31 ] (median (min–max)) patients. Participants were adults with American Society of Anesthesiologists physical statuses categorized as classes I to III.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although dexmedetomidine possesses the hypnotic and sedative effect, bradycardia is the most common side effect of dexmedetomidine administration, especially a large dose of dexmedetomidine. Beloeil H et al reported that dexmedetomidine-based, opioid-free anesthesia had higher rates of severe bradycardia [ 28 ]. A recent study reported prolonged recovery in patients receiving dexmedetomidine, which was explained by over-sedation, hypotension, and bradycardia [ 29 ].…”
Section: Discussionmentioning
confidence: 99%